Parosphromenus barbarae, a new species of Licorice Gourami from Sarawak, Borneo (Teleostei: Osphronemidae) - Tan, Heok Hui; Jongkar, Grinang (Senckenberg Gesellschaft für Naturforschung, 2020)
In Sarawak, there are two main populations of Parosphromenus known, the eastern population linked to the Rejang River basin being P.allani, and the western population linked to the Batang Kayan basin, is herein described as P. barbarae, new species. Parosphromenus barbarae differs from its most similar species, P. allani, in having a distinct black ocellus on caudal-fin base, indistinct dark brown ocellus on posterior base of dorsal-fin; presence of clearly demarcated subdistal hyaline band on anal fin (vs. faint); dorsal-fin rays XI–XIV, 4–5 (total count 15–18, mode 17); anal-fin rays XI–XIII, 6–10 (total count 19–21, mode 21); lateral scales 29–31½ (mode 29).